Enhancing nasal irrigation adherence through a multimodal health communication strategy: a phased improvement study - Lok-Yee Joyce Li; Sheng-Yu Wu; Cheng-Yu Tsai; Arnab Majumdar; Jeffrey Yang; Chien-Ling Su; Cheng-Jung Wu (Scientific Reports, 2026)
Abstract The adherence of chronic rhinitis patients to self-administered treatments is generally very low, which often presents a significant challenge in healthcare. The adherence of chronic rhinitis patients to regular nasal irrigation hygiene care is even lower. Therefore, in this study, we designed, implemented, and evaluated a patient-centered Multimodal Health Communication Strategy intervention, that aimed to improve the adherence to nasal irrigation of adult patients with allergic rhinitis or chronic hypertrophic rhinitis. This was a healthcare quality improvement project conducted from January to July 2025 in the otolaryngology outpatient department of a medical center. The healthcare quality improvement intervention evolved in two stages. The first-stage intervention introduced a “Multimodal Educational Strategy,” combining visual aids, instructional videos, and one-on-one consultation with standard brief verbal instructions. The second-stage intervention, based on patient feedback from the first stage, further optimized the user experience by providing an ergonomic irrigation device and optionally available Herbal Tea Rinse saline solution. The primary outcome measure was that nasal irrigation adherence significantly increased from a baseline of 11.2% to 45.2% after the first stage ( p < 0.001), and further increased to 75.0% after the second stage ( p = 0.013). This represents a 569% relative increase ( p < 0.001) compared to patients who had not undergone the Multimodal Health Communication Strategy intervention. Finally, patients who received the Multimodal Health Communication Strategy educational intervention showed an improvement in knowledge mastery from 51% to 93.8%, and overall satisfaction also significantly increased. The study concluded that low adherence to nasal irrigation is a problem that can be overcome, rather than an insurmountable communication gap between patients and healthcare providers. Systematic patient-centered education through the Multimodal Health Communication Strategy was associated with an improvement in self-nasal irrigation care adherence.